Monitoring method⁃based guided wave for hole-edge crack in key attachment structure of helicopter - WANG Huaji; SHI Liming; DAI Yushan; QIU Lei (Jixie qiangdu, 2025)
ObjectiveThe harsh operational environment of helicopters renders their structures highly susceptible to the initiation and propagation of hole-edge cracks around bolt holes, thereby compromising structural integrity and load-bearing capacity. To monitor hole-edge cracks in helicopter attachment lug structures, piezoelectric guided wave-based structural health monitoring (SHM) techniques are commonly employed. However, due to the difficulty in detecting small cracks at the early stages of propagation and the presence of large through-hole configurations in attachment lug structures, the accuracy of guided wave monitoring remains suboptimal. Therefore, addressing the accuracy issues in crack monitoring of attachment lug structures, this study proposes a piezoelectric guided wave array-based method for hole-edge crack detection.MethodsFirstly, damage feature information was extracted from acquired piezoelectric guided wave array signals encompassing the entire sensor network. Subsequently, a damage alarm threshold was established using a mean-value method to facilitate damage detection. Furthermore, an improved delay-and-sum imaging algorithm was developed based on the specific configuration of the attachment lug structure to optimize probability distribution and achieve precise crack localization. Finally, validation was conducted through test monitoring of crack propagation in attachment lug structures.ResultsTest outcomes demonstrate that the proposed method enables accurate alarm triggering and localization of hole-edge cracks around bolt holes, with localization errors confined within 2.01 mm, thereby confirming the efficacy and precision of the proposed approach.